Sm < 2 + > activated near-infrared fluorescent material as well as preparation method and application thereof

By using Sm2+ as the activation center in the nitride oxide matrix, occupying the pore space of the crystal structure, near-infrared luminescence is achieved, which solves the problems of few activation centers, low efficiency and insufficient stability of existing materials, and is suitable for a variety of advanced applications. application.

CN119331614APending Publication Date: 2025-01-21NANCHANG INST OF TECH

Patent Information

Application Number
CN202411443755.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing near-infrared luminescent materials have fewer activation centers, low efficiency, and insufficient matrix structure stability, which limits their application in high temperature and high humidity environments and bioimaging.

Method used

Sm2+ is used as the activation center to achieve near-infrared luminescence by occupying the pore space of the crystal structure in the nitrogen oxide matrix. The material's chemical composition and structural design are optimized to improve its luminescent performance and stability.

Benefits of technology

It achieves narrow-band near-infrared luminescence, improves the luminous efficiency and the physical and chemical stability of the material, and is suitable for high temperature and high humidity environments and biological imaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005087114490000011
    Figure HDA0005087114490000011
  • Figure HDA0005087114490000012
    Figure HDA0005087114490000012
  • Figure HDA0005087114490000021
    Figure HDA0005087114490000021
Patent Text Reader

Abstract

The invention provides a near-infrared fluorescent material activated by Sm < 2 + > as well as a preparation method and application of the near-infrared fluorescent material. The chemical composition of the fluorescent material is Si < 2-x > Al < x > N < 2 + y > O < 1-y >: Mz, Smm, Lnn, m in the formula is one or more elements of Ba, Sr, Ca and Mg; ln is one or more elements of Bi, Yb, Eu, Nd, Gd, Tb, Dy, Ho, Er, Tm and Pr; 0 < = x < = 0.2, 0.1 < = y < = 0.5, 0 < = z < = 0.5, 0 < = m < = 0.15, and 0 < = n < = 0.1. The luminescent material provided by the invention has a brand new chemical composition, takes Sm < 2 + > as an activation center, and shows a near-infrared luminescence behavior in a gap occupation manner. The fluorescent material can be excited by light within the wavelength range of 300-600 nm, so that narrow-band near-infrared light of 681 nm is emitted, and therefore, the fluorescent material can convert ultraviolet light, purple blue light and green light into near-infrared light. The near-infrared fluorescent material provided by the invention has the advantages of convenient synthesis method and stable chemical properties, and is suitable for the fields of biological imaging, plant growth illumination, white light LEDs, temperature sensors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of inorganic luminescent materials, and in particular relates to a fluorescent material having a novel activation center and realizing near-infrared through gap occupancy, and a preparation method and application thereof. Background Art

[0002] In recent years, inorganic luminescent materials have been widely used in LED and other fields due to their advantages of easy spectrum adjustment, simple preparation process and good stability. Among them, near-infrared luminescent materials (emission wavelength greater than 650nm) have shown great application potential in plant lighting, rapid food detection, night vision imaging and biological imaging in recent years and have attracted much attention [refer to non-patent literature 1]. 3+ and Mn 4+ It is the main activation center of near-infrared luminescent materials at present, but due to the essential factors of dd transition, it has the problem of low absorption efficiency. Therefore, researchers continue to enrich the types of near-infrared luminescent materials by exploring new luminescent centers to meet the growing demand for near-infrared luminescent materials. For example, non-patent document 2 reported that MgIn2O4:Ni with an external quantum efficiency of 34.66% 2+ Broadband near-infrared luminescent material, and the emission peak reaches 1490nm. In addition, as reported in Non-Patent Document 3, MAl2O 19 :Bi 3+ (M=Ca, Sr, Ba) near-infrared luminescent materials, through the optimization of the synthesis atmosphere, obtained near-infrared luminescent materials with emission peaks at 760-808nm. However, such luminescent materials are relatively rare, so it is particularly important to develop new and efficient near-infrared luminescent materials. 2+ Due to its unique fd transition properties, it exhibits a very rich spectrum adjustment ability. By providing it with a strong crystal field environment, it can achieve the characteristics of near-infrared luminescence. 0.5 Ba 0.5 Y2O4:Eu 2+ and (Sr,Ba)3Li4Si2N6:Eu 2+ They can show near-infrared luminescence with peaks at 773 and 830 nm respectively. 2+ There are still few activated near-infrared luminescent materials, so exploring new near-infrared luminescent centers is of great significance for the development of near-infrared luminescent materials.

[0003] Sm 2+ With Eu 2+ It has similar fd transition absorption properties, but its emission will show broadband (df) or linear (ff) near-infrared emission depending on the environment. 2+There are few patent documents on near-infrared luminescent materials as activation centers. There are only some linear emitting oxides and fluorides as matrices. The matrix structure is generally relatively unstable, which restricts the development of near-infrared phosphors [see non-patent document 6]. 2+ There are very few activated near-infrared phosphors, and all of them report luminescence behavior through occupying the crystal lattice [see non-patent literature 7-8]. Non-patent literature 1: LL Zhang, DD Wang, ZD Hao, X. Zhang, GHPan, HJ Wu, JH Zhang.Cr 3+ -Doped Broadband NIR Garnet Phosphor withEnhanced Luminescence and its Application in NIR Spectroscopy.Adv.OpticalMater.,2019,7(12),1900185.

[0004] Non-patent literature 2: F. Zhu, Y. Deng, Y. Gao, J. Qiu. Long-Wavelength Near-Infrared MgIn2O4:Ni 2+ Phosphor with 47.93% IQE and 34.66% EQE for Night VisionLighting, Nonvisual Detection, and Biological Imaging. ACS Mater. Lett., 2024, 6: 4555-4563. Non-patent literature 3: Y. Wei, Z. Gao, X. Yun, H. Yang, Y. Liu, G. Li. Abnormal Bi 3+ -Activated NIR Emission in Highly Symmetric XAl 12 O 19 (X=Ba,Sr,Ca) by SelectiveSites Occupation.Chem.Mater.2022,32(19),8747-8753.

[0005] Non-patent literature 4: Z. Yang, Y. Zhao, Y. Zhou, J. Qiao, YC Huang, M. S. Molokeev, Z. Xia. Giant Red-Shifted Emission in (Sr, Ba) Y2O4:Eu 2+Phosphor Toward BroadbandNear-Infrared Luminescence.Adv.Funct.Mater.,2021,32(1):2103927.

[0006] Non-patent literature 5: S. Li, M. Amachraa, C. Chen, L. Wang, Z. Wang, SPOng, R.-J.

[0007] Non-patent literature 6: T. Zheng, M. Runowski, P. S.Lis,V.Lavin.HugeEnhancement of Sm 2+ Emission via Eu 2+ Energy Transfer in a SrB4O7 PressureSensor.J.Mater.Chem.C,2020,8(14):4810-4817.

[0008] Non-patent document 7: Y.Lv, Y.Li, Z.Li, R.-J.Xie. Near-Infrared Emission of Sm 2+ inOxynitrides.Adv.Optical Mater.,2024,12(10):2302303.

[0009] Non-patent literature 8: J. Pan, Y. Hua, Z. Fan, H. Ma. A Novel Sm 2+ Doped Broadband Far-RedBaAl2Si3O4N4:Sm 2+ Phosphor for Plant Lighting Applications.Opt.Mater.,2023,146:114513. Summary of the invention

[0010] In view of the above-mentioned background technology, the present invention mainly provides a nitrogen oxide-based near-infrared fluorescent material and its preparation method and application which has a simple synthesis method, high efficiency and is easy to industrialize, and is suitable for plant growth lighting, white light LEDs, biological imaging, solar cells, temperature sensors and other fields.

[0011] The present invention is the result of a series of studies based on the above-mentioned understanding, thereby successfully providing a near-infrared fluorescent material. Its composition is shown in formula (I):

[0012] A near-infrared fluorescent material, as shown in formula (I):

[0013] Si 2-x Al x N 2+y O 1-y :M z ,Sm m ,Ln n (I);

[0014] Wherein, M is one or more elements selected from Mg, Ca, Sr, and Ba, and includes at least one element selected from Sr and Ba; Ln is one or more elements selected from Bi, Yb, Eu, Nd, Gd, Tb, Dy, Ho, Er, Tm, and Pr;

[0015] As a preferred embodiment of the present invention, 0≤x≤0.2, 0.1≤y≤0.5, 0≤z≤0.5, 0≤m≤0.15, and 0≤n≤0.1.

[0016] The present invention also discloses a method for preparing a near-infrared fluorescent material, comprising:

[0017] The near-infrared luminescent material is obtained by mixing an M precursor, a Sm precursor, a Ln precursor, an Al precursor and a Si precursor and performing a high-temperature solid-phase reaction.

[0018] The molar ratio of Si, Al, M, Sm, Ln and Si in the M precursor, Sm precursor, Ln precursor, Al precursor and Si precursor is 2-x:x:z:m:n; 0≤x≤0.2, 0.1≤y≤0.5, 0≤z≤0.5, 0≤m≤0.15, 0≤n≤0.1.

[0019] Furthermore, the purity of the M precursor, Sm precursor, Ln precursor, Al precursor and Si precursor is no less than 99.5%.

[0020] Furthermore, the steps are specifically as follows:

[0021] The M precursor, Sm precursor, Ln precursor, Al precursor and Si precursor are mixed in a certain proportion and reacted at high temperature in a reducing atmosphere. After the final product is cooled to room temperature, it is ground to obtain a near-infrared luminescent material.

[0022] Further, the M precursor is one or more of M carbonate, M oxalate, M nitrate, M sulfate, M chloride and M oxide;

[0023] The Sm precursor is one or more of Sm carbonate, Sm oxide, Sm sulfide, Sm halide, Sm boride, Sm oxalate and Sm nitrate;

[0024] The Ln precursor is one or more of Ln carbonate, Ln oxide, Ln sulfide, Ln chloride, Ln oxalate and Ln nitrate;

[0025] The Al precursor is one or more of Al oxide, Al nitride, Al chloride, Al nitrate and Al carbonate;

[0026] The Si precursor is one or more of Si powder, Si oxide, and Si nitride;

[0027] Furthermore, the reducing atmosphere is one of nitrogen, argon, argon-hydrogen or a nitrogen-hydrogen mixed gas.

[0028] Furthermore, the temperature of the high temperature solid phase reaction is 1200-1700° C.; and the time of the high temperature solid phase reaction is 1-6 hours.

[0029] The present invention also discloses an application of any of the above-mentioned near-infrared fluorescent materials in biological imaging, white light LEDs, and temperature sensors.

[0030] The present invention achieves the following beneficial effects: The present invention provides a narrow-band near-infrared fluorescent material with a novel luminescent center and a preparation method and application thereof. The near-infrared fluorescent material has a novel luminescent center and a completely new chemical composition, and no relevant literature reports its luminescent properties. In addition, compared with conventional near-infrared luminescent materials, the near-infrared fluorescent material with Sm 2+ As the activation center, and by occupying the pore space of the crystal structure, it exhibits near-infrared luminescence. In addition, the near-infrared luminescent material uses nitrogen oxide as a matrix, which makes it very stable and can be used in some special conditions (such as high temperature and high humidity), as well as in the fields of biological imaging, plant growth lighting, white light LEDs, temperature sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1This is the X-ray diffraction pattern of the near-infrared luminescent material obtained in Example 4 of the present invention;

[0032] Figure 2 The normalized emission spectrum of the near-infrared luminescent material obtained in Example 4 of the present invention under 332 nm excitation and the normalized excitation spectrum monitored at 681 nm;

[0033] Figure 3 The normalized emission intensity diagram measured at different temperatures for Example 4;

[0034] Figure 4 This is the X-ray diffraction pattern of the near-infrared luminescent material obtained in Example 14 of the present invention;

[0035] Figure 5 The normalized emission spectrum of the near-infrared luminescent material obtained in Example 14 under 333 nm excitation and the normalized excitation spectrum monitored at 681 nm. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention will be described in detail below in conjunction with the embodiments of the present invention, and the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.00375, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into an Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent materials.

[0039] The optical properties of the near-infrared luminescent material obtained in Example 1 were analyzed using a fluorescence spectrometer, which showed a narrow-band emission peak at 681 nm under excitation by 332 nm ultraviolet light, indicating that the phosphor can be excited by ultraviolet light to emit red light, that is, the fluorescent material can convert ultraviolet light into near-infrared light.

[0040] Example 2

[0041] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.0075, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into an Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm2O3 was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0042] The fluorescent material obtained in Example 2 was analyzed using a fluorescence spectrometer. Its emission spectrum under 332 nm ultraviolet light excitation showed no significant change compared with Example 1 except that the intensity was slightly increased.

[0043] Example 3

[0044] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.015, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into an Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared luminescent materials.

[0045] The fluorescent material obtained in Example 3 was analyzed by using a fluorescence spectrometer, and its emission spectrum under 332 nm ultraviolet light excitation was found to have an intensity greater than that of Example 2.

[0046] Example 4

[0047] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.03, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0048] The test results of this embodiment are shown in Figure 1 , indicating that the sample has the same diffraction result as ICSD#66540. The fluorescent material obtained in Example 4 was analyzed using a fluorescence spectrometer, and the results are shown in Figure 2The emission peak under 332nm ultraviolet light excitation is located at 681nm. Compared with the samples in Example 1, Example 2, and Example 3, the emission peak remains unchanged, and its intensity is significantly increased.

[0049] At the same time, the thermal stability test of Example 4 was carried out, that is, the normalized stability emission spectrum was as follows: Figure 3 As shown, it can be seen that the sample in Example 4 has stable chemical properties.

[0050] Example 5

[0051] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.045, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0052] The fluorescent material obtained in Example 5 was analyzed by a fluorescence spectrometer, and its emission spectrum was obtained under 332nm ultraviolet light excitation. Compared with the emission spectrum of Example 4, Example 3 and Example 2, there was no obvious change.

[0053] Example 6

[0054] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.06, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared fluorescent materials.

[0055] The fluorescent material obtained in Example 6 was analyzed by a fluorescence spectrometer, and its emission spectrum was obtained under 332nm ultraviolet light excitation. Compared with the shape of the emission spectrum of Example 5, there was no obvious change.

[0056] Example 7

[0057] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 2:1:0.075, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, it was cooled to room temperature with the furnace and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0058] The fluorescent material obtained in Example 7 was analyzed using a fluorescence spectrometer, and its emission spectrum was obtained under 332nm ultraviolet light excitation, which showed no significant change compared with Example 3.

[0059] Example 8

[0060] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 1:1:0.03, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm2O3 was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0061] The fluorescent material obtained in Example 8 was analyzed by a fluorescence spectrometer. Its emission spectrum under 332 nm ultraviolet light excitation showed no significant change compared with Example 4 except that the emission intensity was decreased.

[0062] Example 9

[0063] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure) and Sm2O3 (analytical pure) of 3:1:0.03, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, the furnace was cooled to room temperature, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0064] The fluorescent material obtained in Example 9 was analyzed by a fluorescence spectrometer. Its emission spectrum under 332 nm ultraviolet light excitation showed no significant change compared with that in Example 8 except that the intensity was enhanced.

[0065] Example 10

[0066] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure), Sm2O3 (analytical pure) and CeO2 (analytical pure) of 2:1:0.03:0.0075, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared fluorescent material.

[0067] The fluorescent material obtained in Example 10 was analyzed by fluorescence spectrometer, and its emission spectrum and Figure 4 Compared with the previous study, there is no obvious change. From its excitation spectrum, it can be found that Ce 3+ The introduction of can improve the blue light excitation efficiency of the near-infrared material.

[0068] Embodiment 11

[0069] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure), Sm2O3 (analytical pure) and CeO2 (analytical pure) of 2:1:0.03:0.015, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, it was cooled to room temperature with the furnace, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0070] The fluorescent material obtained in Example 11 was analyzed using a fluorescence spectrometer, and its emission spectrum obtained under 332 nm ultraviolet light excitation showed no significant change compared with Example 10 except for the emission intensity.

[0071] Example 12

[0072] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure), Sm2O3 (analytical pure) and CeO2 (analytical pure) of 2:1:0.03:0.03, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, and sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min). After the reaction was completed, it was cooled to room temperature with the furnace, and the required Sm was obtained after grinding in an agate mortar. 2+ Doped with near-infrared fluorescent material.

[0073] The fluorescent material obtained in Example 12 was analyzed using a fluorescence spectrometer, and its emission spectrum under 332nm ultraviolet light excitation showed no significant change compared with Example 11 except for the emission intensity.

[0074] Embodiment 13

[0075] According to the molar ratio of Si (analytical pure), SiO2 (analytical pure), Sm2O3 (analytical pure) and CeO2 (analytical pure) of 2:1:0.03:0.045, the above raw materials were ground and mixed in an agate mortar, dried and then loaded into a steel Al2O3 crucible, sintered at 1450°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared fluorescent materials.

[0076] Embodiment 14

[0077] According to the molar ratio of Si3N4 (analytical pure), SiO2 (analytical pure), and Sm2O3 (analytical pure) of 1:1:0.08, the above raw materials were ground and mixed in an agate mortar, dried, and then loaded into a steel Al2O3 crucible, and sintered at 1650°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared fluorescent materials.

[0078] The test results of this embodiment are shown in Figure 4 , indicating that the sample has the same diffraction main peak as Example 4. The optical properties of the near-infrared luminescent material obtained in Example 14 were analyzed using a fluorescence spectrometer. The results are shown in Figure 5 , it shows a narrow-band emission peak at 681nm under the excitation of 333nm ultraviolet light, indicating that the phosphor can be excited by ultraviolet light to emit red light, that is, the fluorescent material can convert ultraviolet light into near-infrared light.

[0079] Embodiment 15

[0080] According to the molar ratio of Si3N4 (analytical pure), SiO2 (analytical pure), and Sm2O3 (analytical pure) of 1:1:0.06, the above raw materials were ground and mixed in an agate mortar, dried, and then loaded into a steel Al2O3 crucible, and sintered at 1650°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0081] The optical properties of the near-infrared luminescent material obtained in Example 15 were analyzed using a fluorescence spectrometer, and a narrow-band emission peak at 681 nm was shown under excitation of 332 nm ultraviolet light, indicating that the phosphor can be excited by ultraviolet light to emit red light, that is, the fluorescent material can convert ultraviolet light into near-infrared light.

[0082] Example 16

[0083] According to the molar ratio of Si3N4 (analytical pure), SiO2 (analytical pure), and Sm2O3 (analytical pure) of 1:1:0.04, the above raw materials were ground and mixed in an agate mortar, dried, and then loaded into a steel Al2O3 crucible, and sintered at 1650°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0084] The fluorescent material obtained in Example 16 was analyzed using a fluorescence spectrometer, and its emission spectrum obtained under 332nm ultraviolet light excitation showed no significant change compared with Example 15 except for the emission intensity.

[0085] Embodiment 17

[0086] According to the molar ratio of Si3N4 (analytical pure), SiO2 (analytical pure), and Sm2O3 (analytical pure) of 1:1:0.02, the above raw materials were ground and mixed in an agate mortar, dried, and then loaded into a steel Al2O3 crucible, and sintered at 1650°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0087] The fluorescent material obtained in Example 17 was analyzed using a fluorescence spectrometer, and its emission spectrum under 332nm ultraviolet light excitation showed no significant change compared with Example 16 except for the emission intensity.

[0088] Embodiment 18

[0089] According to the molar ratio of Si3N4 (analytical pure), SiO2 (analytical pure), and Sm2O3 (analytical pure) of 1:1:0.01, the above raw materials were ground and mixed in an agate mortar, dried, and then loaded into a steel Al2O3 crucible, and sintered at 1650°C for 4 hours in a high-temperature furnace in a H2 / N2 mixed gas (gas content ratio of H2:N2=5:95, gas flow rate of 100mL / min), cooled to room temperature with the furnace after the reaction, and ground in an agate mortar to obtain the required Sm 2+ Doped with near-infrared luminescent materials.

[0090] The fluorescent material obtained in Example 18 was analyzed using a fluorescence spectrometer, and its emission spectrum under 332nm ultraviolet light excitation showed no significant change compared with Example 17 except for the emission intensity.

[0091] In summary, the present invention provides a new Sm 2+ By occupying the lattice pores (due to the cation Si 4+ The radius [0.26-0.4nm] is much smaller than Sm 2+ The radius of Sm is [1.22-1.32nm]), which cannot achieve occupation substitution, and the pore radius is larger than Sm 2+ The near-infrared material that exhibits near-infrared luminescence by optimizing the composition, fine-tuning the structure and transferring energy is used to improve the luminescence performance of the near-infrared luminescent material. Such unique luminescence behavior plays an important role and has application prospects in enriching the types of near-infrared luminescent materials. In addition, the present invention uses Sm 2+ The nitrogen oxide narrow-band near-infrared luminescent material prepared as the activation center can solve the problems existing in the existing near-infrared luminescent material research, such as few luminescent centers, low efficiency, and poor physicochemical stability, thereby promoting the nitrogen oxide near-infrared luminescent material to have broad application prospects in some special conditions (such as high temperature and high humidity) as well as in white light LEDs and bio-imaging optical temperature sensors.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A near-infrared fluorescent material, as shown in formula (I): Si 2-x Al x N 2+y O 1-y :M z , Sm m , Ln n (I); in, M is one or more elements selected from Mg, Ca, Sr, and Ba, and includes at least one element selected from Sr and Ba; Ln is one or more elements selected from Bi, Yb, Eu, Nd, Gd, Tb, Dy, Ho, Er, Tm, and Pr.

2. The fluorescent material according to claim 1, characterized in that Said 0≤x≤0.2, 0.1≤y≤0.5, 0≤z≤0.5, 0≤m≤0.15, 0≤n≤0.

1.

3. A method for preparing the near-infrared fluorescent material as claimed in claim 1 or 2, characterized in that: include: A near-infrared fluorescent material is obtained by mixing an M precursor, an Sm precursor, an Ln precursor, an Al precursor, and a Si precursor and performing a high-temperature solid-phase reaction; The molar ratio of Si, Al, M, Sm, and Ln in the M precursor, Sm precursor, Ln precursor, Al precursor, and Si precursor is 2-x:x:z:m:n; 0≤x≤0.2, 0.1≤y≤0.5, 0≤z≤0.5, 0≤m≤0.15, 0≤n≤0.

1.

4. The preparation method according to claim 3, characterized in that: The purity of the M precursor, Sm precursor, Ln precursor, Al precursor and Si precursor is no less than 99.5%.

5. The preparation method according to claim 3, characterized in that: The steps are specifically as follows: The M precursor, Sm precursor, Ln precursor, Al precursor and Si precursor are mixed and subjected to a high-temperature solid-phase reaction in a reducing atmosphere. After the final product is cooled to room temperature, it is ground to obtain a near-infrared luminescent material.

6. The preparation method according to claim 5, characterized in that: The M precursor is one or more of M carbonate, M oxalate, M nitrate, M sulfate, M chloride and M oxide; The Sm precursor is one or more of Sm carbonate, Sm oxide, Sm sulfide, Sm halide, Sm boride, Sm oxalate and Sm nitrate; The Ln precursor is one or more of Ln carbonate, Ln oxide, Ln sulfide, Ln chloride, Ln oxalate and Ln nitrate; The Al precursor is one or more of Al oxide, Al nitride, Al chloride, Al nitrate and Al carbonate; The Si precursor is one or more of Si powder, Si oxide, and Si nitride.

7. The preparation method according to claim 5, characterized in that: The reducing atmosphere is one of nitrogen, argon, argon-hydrogen or nitrogen-hydrogen mixed gas.

8. The preparation method according to claim 5, characterized in that: The temperature of the high-temperature solid phase reaction is 1200-1700° C.; the time of the high-temperature solid phase reaction is 1-6 hours.

9. Application of the near-infrared fluorescent material according to claim 1 or 2 or the near-infrared fluorescent material prepared by the preparation method according to any one of claims 3 to 8 in biological imaging, plant growth lighting, white light LED, and temperature sensor.

Citation Information

Patent Citations

  • Sm &lt; 2 + &gt;-activated broadband near-infrared luminescent material as well as preparation method and application thereof

    CN115572600A

  • Process for producing a ß-SiAION phosphor

    DE112009001977T5

Cited By

  • Near-infrared luminescent material as well as preparation method and application thereof

    CN121343595A

  • A near-infrared luminescent material, a preparation method and application thereof

    CN121343595B